2012
DOI: 10.1039/c2cc16101j
|View full text |Cite
|
Sign up to set email alerts
|

Visible light driven hydrogen production from a photo-active cathode based on a molecular catalyst and organic dye-sensitized p-type nanostructured NiO

Abstract: A molecular device with a photocathode for hydrogen generation has been successfully demonstrated, based on an earth abundant and inexpensive p-type semiconductor NiO, an organic dye P1 and a cobalt catalyst Co1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
245
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 249 publications
(252 citation statements)
references
References 39 publications
5
245
2
Order By: Relevance
“…The first demonstration of this approach was reported by Nann et al [106] when they adsorbed a Fe 2 S 2 (CO) 6 , the simplest mimicking equivalent of the [FeFe]-hydrogenase, with a mesoporous p-type InP photoelectrode (figure 10d). Cobaloxime, a bioinspired equivalent of hydrogenases, was also successfully integrated with an organic dyesensitized-NiO or a Ru-dye-sensitized TiO 2 electrode via either non-covalent [113] or covalent grafting [114]. However, these photocathodes showed moderate efficiency; typical photocurrents of only a few microamperes were obtained.…”
Section: Hybrid Photocatalysts For Proton Reduction and Hydrogen Evolmentioning
confidence: 99%
“…The first demonstration of this approach was reported by Nann et al [106] when they adsorbed a Fe 2 S 2 (CO) 6 , the simplest mimicking equivalent of the [FeFe]-hydrogenase, with a mesoporous p-type InP photoelectrode (figure 10d). Cobaloxime, a bioinspired equivalent of hydrogenases, was also successfully integrated with an organic dyesensitized-NiO or a Ru-dye-sensitized TiO 2 electrode via either non-covalent [113] or covalent grafting [114]. However, these photocathodes showed moderate efficiency; typical photocurrents of only a few microamperes were obtained.…”
Section: Hybrid Photocatalysts For Proton Reduction and Hydrogen Evolmentioning
confidence: 99%
“…Nevertheless, in all cases, the photocurrents proved very stable with time. We thus decided to compare the aqueous acetate buffer conditions examined here with phosphate buffer conditions more typically used in the literature [27,51,52]. Figure 8 compares the PEC performance of the same electrode recorded first in acetate buffer ( pH 4.5, black trace) and then in phosphate buffer ( pH 7, red trace).…”
Section: Photoelectrochemical Properties Of Dye-sensitized Nio Filmsmentioning
confidence: 99%
“…One of the most obvious is water splitting. In 2012, Li et al reported the use of their P1 sensitizer on NiO for water reduction to generate H2 gas [202]. This was accomplished with the aid of a cobalt co-catalyst and triethanolamine as a sacrificial electron donor.…”
Section: Sensitized Photocathodes For Water Splittingmentioning
confidence: 99%